2020
DOI: 10.3390/ijerph17238862
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking the ‘Business Model’ for Fortification Initiatives in Low- and Middle-Income Countries: Stakeholder Identified Drivers of Success and Constraints to Progress

Abstract: Background: Initiatives to tackle micronutrient deficiencies (MNDs) in low-and middle-income countries (LMICs) have increased steadily in recent years. Commodities such as staple foods (e.g., cereals) and condiments (e.g., salt) have been targeted as ‘vehicles’ for industrial fortification through numerous projects and initiatives. However, mixed experiences with delivery, coverage and sustainability have been found. Methods: Using an online survey of 71 key stakeholders (from 35 countries) consisting of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…It has been well documented that an important contributor to success of fortification initiatives are standards and national level agents that are able to enforce necessary regulations [ 2 ]. Lalani et al [ 5 ] also showed in a study of stakeholders involved in industrial fortification from 35 countries that standards, large-scale production and in-factory testing were among the key factors associated with success/coverage of the target market in LMICs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been well documented that an important contributor to success of fortification initiatives are standards and national level agents that are able to enforce necessary regulations [ 2 ]. Lalani et al [ 5 ] also showed in a study of stakeholders involved in industrial fortification from 35 countries that standards, large-scale production and in-factory testing were among the key factors associated with success/coverage of the target market in LMICs.…”
Section: Discussionmentioning
confidence: 99%
“…This is crucial to future uptake and success of food fortification initiatives because of the importance of viability (financial, technical, social) to achieving the desired public health impacts. This issue of viability is, to date, is largely absent from the literature [ 4 ] and evidently valued by practitioners [ 5 ]. Furthermore, [ 6 ] explains at a higher level the potential impact of food fortification on public health (e.g., please refer to the ‘Impact model’ developed by [ 6 ]).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of food fortification initiatives, PPPs can provide funding mechanisms and technical support, and advocate for the development of local government policies and regulations that can enable the environment for SMEs to be integrated as key change agents in the food supply chain. Crucial elements for effective food fortification include a business plan for self-sustainability, mandatory regulation and local standards, compliance monitoring, market research and the availability of premixes [78]. Private and public partners can support SMEs in these areas to help them optimize their food fortification practices (Figure 1) [79].…”
Section: Ppps As a Possible Solution To Overcome The Burden Of Malnut...mentioning
confidence: 99%